Theoretical and methodological aspects to analyze the constitution of the education policy academic field in Brazil - Silvana Stremel (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2017)
This paper aims at presenting the methodological trajectory and the study sources for the analysis of the formation of an education policy academic field in Brazil. It is based on Bourdieu‟s contributions regarding the fields‟ formation and functioning, as well as methodological issues for the analysis of a certain object of study. In relation to that author‟s contributions, a set of aspects that contributed to the structure of the education policy academic field is presented as it is used as a source for the study of this field background in the Brazilian context. Based on the theoretical background and the survey of sources, this field was seen as an institutionalized area that has been acquiring legitimacy with the creation of subjects, journals, groups of study and research lines, research nets, conferences, groups of work in scientific entities and specific conferences, among others.